2017
DOI: 10.1007/s00417-017-3722-x
|View full text |Cite
|
Sign up to set email alerts
|

Ganglion cell layer segmentation and the two-flash multifocal electroretinogram improve structure function analysis in early glaucoma

Abstract: PurposeTo improve structure-function analysis in primary open-angle glaucoma (POAG) by including the two-global flash multifocal electroretinogram (2F–mfERG) and macular ganglion cell layer segmentation.MethodsTwenty-five glaucoma patients (six pre-perimetric (PPG), 19 POAG) and 16 controls underwent 2F–mfERG, optical coherence tomography (OCT), and standard automated perimetry (SAP). For 2F–mfERG, the root mean square was calculated for the focal flash response at 15–45 ms (DC) and the global flash responses … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 53 publications
0
8
0
Order By: Relevance
“…In addition to a standard examination, Brandao et al applied visual field analysis, GCL-IPL complex measurement, and the 2F-mfERG test to the participants in their study and evaluated the relationship of these findings with each other. The authors determined that in patients with early-stage glaucoma, the 2F-mfERG and GCL-IPL tests were the diagnostic tools with the highest probability of detecting glaucomatous dysfunction, and combining functional and structural tests is valuable in terms of early diagnosis [11]. Similarly, Talamini et al [27] showed that although the use of OCT segmentation analysis in glaucoma was beneficial in increasing OCT sensitivity, there were still many patients with normally appearing retinas, but mfERG was able to document retinal dysfunction in these patients and combining these two tests had diagnostic value.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition to a standard examination, Brandao et al applied visual field analysis, GCL-IPL complex measurement, and the 2F-mfERG test to the participants in their study and evaluated the relationship of these findings with each other. The authors determined that in patients with early-stage glaucoma, the 2F-mfERG and GCL-IPL tests were the diagnostic tools with the highest probability of detecting glaucomatous dysfunction, and combining functional and structural tests is valuable in terms of early diagnosis [11]. Similarly, Talamini et al [27] showed that although the use of OCT segmentation analysis in glaucoma was beneficial in increasing OCT sensitivity, there were still many patients with normally appearing retinas, but mfERG was able to document retinal dysfunction in these patients and combining these two tests had diagnostic value.…”
Section: Resultsmentioning
confidence: 99%
“…Studies have shown that in glaucoma patients, the inner plexiform layer (IPL), especially the macular ganglion cell layer (GCL) is affected [7,8,9,10]. Strong correlations have been demonstrated between the GCL + IPL complex and multifocal electroretinography (mfERG) measurements [4,11].…”
Section: Introductionmentioning
confidence: 99%
“…However, bipolar cells in the inner retinal layer also contribute to the mf-ERG wave components. Many studies on this issue report that mf-ERG can provide valuable information concerning progression, especially in the early stages of glaucoma (29,30). These studies suggest that during the early stages of glaucoma, electrical activity may be affected before anatomical and morphological changes in the macula.…”
Section: Discussionmentioning
confidence: 99%
“…We calculated the N/T-namely, the ratio of the mfERG P1 amplitudes of the rst slice of the second-order kernel (Figure 2b)-in the nasal hemisphere of the VF (i.e., temporal hemisphere of the retina) and compared with that in the temporal hemisphere of the VF (i.e., nasal hemisphere of the retina) in the central 5°. We also calculated the correlations between the thresholds obtained from the corresponding VF area, OCT parameters, and the N/T [18,19].…”
Section: Nasal To Temporal Amplitude Ratio Analyses Of Mferg Scansmentioning
confidence: 99%
“…To compare the mfPhNR/B with the corresponding VF ndings, we measured the thresholds with the HFA 30-2 and averaged for the same sectors according to the distance from the macula within the central 20° ( Figure 4). We also calculated the correlations between the thresholds of the corresponding VF area, the mfPhNR/B, and OCT parameters [18,19].…”
Section: Mfphnr/b Analysesmentioning
confidence: 99%